In memoriam of František Balát on the centenary of his birth - Sychra, Oldřich; Sychra, Jan (Zootaxa, 2025)
This paper is dedicated to the memory of the prominent Czechoslovak ornithologist and phthirapterist František Balát (22 July 1925–20 April 1992), who would have celebrated his centenary this year. Both published and unpublished data, and memories from his colleagues and friends are included. In particular, we discuss his work in the field of chewing lice (Phthiraptera) as a leading world expert. His intensive louse collecting and knowledge of their avian hosts, made a great contribution to knowledge of distribution and biology of many European chewing louse species. The origins and a brief description of Balát’s louse collection is given.